The moderator role of procrastination in the relationship between academic stress and psychological well-being in undergraduate students - Delgado-Tenorio, Ariana L. (2021)
The present study aims to analyze the association between academic stress and psychological well-being, and the role of academic procrastination in this relationship, in a sample of undergraduate students. The sample was composed by 391 undergraduate students from various universities in Lima Metropolitana - Peru. The Spanish adaptation of Ryff’s Psychological Well-being Scales (SPWB), The Cognitive Systemic Inventory (SISCO SV-21) and the Academic Procrastination Scale (EPA). Results show that procrastination and academic stress are negatively related to psychological well being. Moreover, presence of stressors and symptoms associated with academic stress, and procrastination are relevant predictors of psychological well-being; however, the interaction between both variables did not represent a significant effect; therefore, it is concluded that there is no moderating effect of academic procrastination in the relationship between academic stress and psychological well-being. Instead, procrastination was found to play a moderating role in the relationship between stressors and the development of symptoms associated with academic stress.